Failure Analysis of a Rear-Sprocket Mounting (Nap Gear) Bolt in a 145 cc Motorcycle - Ambo Ardy Pranowo; Andiyanto Andiyanto; Ruben Sanilo; Hammam Abdirrazzaq Ats Tsaqif (Multidisciplinary Innovations and Research in Applied Engineering, 2026)
Rear-sprocket mounting bolts, referred to in this study as nap gear bolts, transmit torque from the rear sprocket assembly to the wheel hub through the damper/bushing interface and may experience repeated transverse shear and bending loads. This study investigates the fracture of a rear-sprocket mounting (nap gear) bolt from a 145 cc motorcycle to determine its material characteristics, fracture mechanism, and mechanical cause of failure. The investigation combined macro-fractographic observation, spark-emission chemical composition testing, optical metallography, Vickers microhardness testing, and finite element analysis of a three-dimensional bolt model. The measured chemistry was consistent with the SAE 1015 low-carbon steel composition range, with 0.137 wt.% C and a ferrite-pearlite microstructure; however, the grade designation is reported as a chemical-consistency assessment rather than a mill-certified material identification. No abnormal microstructural difference or surface-hardening layer was observed between the failed and intact bolts. The hardness values were 179-190 HV0.5 for the failed bolt and 169-183 HV0.5 for the intact bolt. Fractography identified a proposed crack-initiation region, a crack-propagation region with beachmark-like macroscopic features, and a final-fracture region. Finite element analysis predicted a local maximum stress intensity, defined as the difference between the maximum and minimum principal stresses, of 529.6 MPa at the fracture location; the corresponding maximum shear stress was 264.8 MPa. The failure is therefore attributed to fatigue initiated at a stress-concentrated region, while the available evidence does not indicate that material selection or gross metallurgical abnormality was the primary cause.